Webtoons as Pedagogical Tools: Foundation TESL Students’ Perceptions in Enhancing Interest in Reading - Roslan, Siti Aisyah; Damia Aqmar Hisham; Melissa Qristal Abdullah (Advances in Humanities and Contemporary Studies, 2025)
Webtoons, digital comics originating in South Korea, have been translated into English and are characterised by visually appealing images and vertical scroll formats. In recent years, webtoons have gained popularity as an interactive and engaging reading medium. This study investigates the perceptions of 50 students from Foundation for B.ED TESL programme in a private university in Selangor towards the use of English webtoons to increase their interest and motivation in reading English. The data was collected using structured questionnaires and analysed using Statistical Package for the Social Sciences (SPSS) version 27. This study shows that English webtoons significantly increase ESL students’ reading interest and skills. The visual appeal of webtoons is a key factor in this positive outcome, highlighting the value of using engaging materials in ESL instruction.